The position of the religious authority in Najaf on the nomination of Faisal bin Al-Hussein as king of Iraq and his coronation in 1921 (Journal of the College of Basic Education, 2023)
The religious authority in Najaf is considered one of the ancient religious institutions in Islamic countries, as it dates back to the fifth century AH, and was distinguished by unparalleled advantages, such as financial and administrative independence from governments and ruling regimes, by virtue of the fact that it receives legitimate funds from its followers, and its religious and social influence on its followers Be it inside or outside Iraq. By virtue of it being an extension of the doctrine of the Imamate - so to speak - one of the fundamentals of religion among the Twelver Shiite Muslims, and therefore its social weight and its political implications cannot be avoided when talking about the contemporary history of Iraq, especially if the talk is about events and political developments prior to the establishment of the Iraqi state The year 1921 and the years that witnessed the consolidation of its institutions .. Therefore, the position of the religious authority on the nomination and coronation of a king for Iraq represents a great importance for historical research. We assume that the core of the opposition to the British project in Iraq, which changed after the twentieth revolution from direct British military rule to the establishment of a state with a monarchy system subject to full British influence, is the religious reference and not changing its principled position on British control over Iraq in any way, but that principle that reached The degree of idealism was inconsistent with the political and military reality imposed by the control of a superpower at the time on Iraq. It was able to exploit the discrepancy in positions between the various segments of society, which the religious authority realized late, but despite that it did not change its principled positions, as an ancient religious body with its constants. The research was divided into an introduction, three sections, and a conclusion with the most important conclusions.The first topic studied the position of the religious authority on the nomination of a king over Iraq from the Sharifian family that used to rule the Hijaz. It has that Faisal will be an Iraqi king under the mandate authority. As for the second topic, it touched on the candidates for the throne and how Faisal bin Al-Hussein was chosen as king of Iraq by the British authorities and the reasons that prompted them to make that choice. While the third topic dealt with the position of the religious authority on the coronation of Faisal and the reasons that prevented it from issuing any position opposing that coronation, although it did not welcome the coronation of any king under the mandate, which it considered colonialism in a new dress that must be disposed of, in line with its principled positions on the British occupation of Iraq.